ANALISIS KESALAHAN MENYELESAIKAN SOAL CERITA BANGUN RUANG SISI LENGKUNG BERDASARKAN METODE NEWMAN PADA SISWA BERGAYA BELAJAR AUDITORIAL - Setiawan, Toto Bara; Martina, Agfa; Susanto, S (Department of Mathematics Education , University of Jember, 2018)
This research aims to analyze the errors which are made by students who use auditorial learning style in solving the problem about curved-side geometry based on Newman Method. There are 3 instruments which are used, they are learning style's questionnaire that is a modification of learning style's questionnaire (VAK) that was developed by V Chislett MSc & A Chapman to gain students' subject uses auditorial learning style, the problems which consist of 3 problems in form of stories about curved-side geometry to know the students' error by using the indicators for each error based on Newman method, and interview guideline the factors which cause the errors. Based on the result of the analysis of learning style's questionnaire which was given to IX-H grade students of SMPN 2 Genteng, it showed that there were 10 students with visual learning style, 10 students with auditorial learning style, and 16 students with kinesthetic learning style. The least percentage of error was 6,66% for reading error, while the most error was for transform error (problem transformation) with 79,99%. Keywords: Newman's error analysis, learning style, students with auditorial learning style